Cell therapy for cardiac diseases. Issue 4 (16th April 2018) - Tseliou, E.
Abstract: Cardiac injury and loss of functional cardiomyocytes result in cardiac pump failure, the leading cause of morbidity and mortality in the world. Endogenous regeneration of the injured heart holds great promise but is very limited in the human heart. Various strategies have been developed to boost replacement of the lost cardiomyocytes including stem cells and cellular reprogramming. In this review we will discuss the progress in cardiac regeneration field, the advantages and disadvantages of each cell type and how a combinatorial approach with regards to current drug treatment could enhance cardiac regeneration. Abstract : Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/5936020/Activity.aspx